2018
DOI: 10.1108/bpmj-05-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Customer influence on supply chain management strategies

Abstract: Purpose Customers influence companies’ operational strategies and supply chain (SC) processes. In this vein, signals coming from the market must be translated into proper strategies in terms of production and supply. The purpose of this paper is to provide an understanding on how to transform customers’ expectations into SC decisions. The yacht industry, encompassing both technical and emotional peculiarities, becomes this study’s driven focus to interrogate the interrelationship between supply and demand. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The main investment areas include the systems for development of fast response and quality management (13)(14). Single sourcing strategies assure product quality (15) with enough cost efficiency. However, selection of supplier is main and important strategic issue for supply chain management (16)(17).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The main investment areas include the systems for development of fast response and quality management (13)(14). Single sourcing strategies assure product quality (15) with enough cost efficiency. However, selection of supplier is main and important strategic issue for supply chain management (16)(17).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Both flexibility and collaboration with suppliers, therefore, play an essential role when it comes to fulfilling demand requirements. Outsourcing is employed to access extremely rare or ultimate quality materials (Brun and Karaosman, 2019).…”
Section: Supply Chain Configuration Elementsmentioning
confidence: 99%
“…Wang et al (2016) have observed that interpersonal relationships such as personal tenderness, communications, and believability, are key elements for improving integration among SC members. Brun and Karaosman (2019) stated that single sourcing strategies give quality products with cost effectiveness. Selection and evaluation of suppliers is a critical and strategic issue for SCM of Indian SMEs .…”
Section: Scm Practicesmentioning
confidence: 99%